If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.78g + -6 = 0.23 Reorder the terms: -6 + 1.78g = 0.23 Solving -6 + 1.78g = 0.23 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 1.78g = 0.23 + 6 Combine like terms: -6 + 6 = 0 0 + 1.78g = 0.23 + 6 1.78g = 0.23 + 6 Combine like terms: 0.23 + 6 = 6.23 1.78g = 6.23 Divide each side by '1.78'. g = 3.5 Simplifying g = 3.5
| -4x+6(2x-7)=-31-2x | | 4x+50=x+10 | | g(x)=-5x+2 | | 128+1x=24 | | x*2+x-5=45 | | 2x+40=y | | 10y-7y-11=21.22 | | 13y-8y-4=47.60 | | 3x-8=x+5 | | -2(3b+3)=3b+39 | | 17x=19x | | 14y-12y=6 | | 3x-4=11x-27 | | 15y-11y=12 | | x+27=4 | | 3x+13x=80 | | 2x+4y=-23 | | 13x-6=11x+14 | | 12y-10y=8 | | 5x+17=15x+3 | | y+15-8=12 | | 27x-5=26x | | 4x+8+1=9 | | 12m+46=1138.00 | | 50x-2=49x | | -2(x+5)-2=-8+4 | | 6z+4z=9z-4 | | X-16=16+2x | | 7x+5=8x-5 | | 34+6=63 | | 23+1x=36 | | 6x+8=8x-2 |